ANALISIS “SOME ONE TO TALK” TERHADAP KESEHATAN MENTAL GEN Z DENGAN LOVE LANGUAGE “WORD OF AFFIRMATION” - Muhammad Zaqil Mubarok; Khadijah (STKIP Subang, 2025)
Generation Z, those born between 1997 and 2012, face unique challenges in an increasingly digital and complex world. Academic pressures, social media demands, and uncertainty about the future can all have a negative impact on their mental health. Amidst these challenges, it is important to understand how certain factors can impact the mental well-being of Generation Z. One important factor to examine is the role of